Smart modern hydroponic product / Nazeem Shahiry Mohd Ayub - Mohd Ayub, Nazeem Shahiry (Universiti Teknologi MARA, Kedah, 2024)
In the face of urbanization, living spaces have become increasingly compact, necessitating innovative solutions for gardening and temperature management. This project explores the design of a hanging hydroponic product tailored for small space balconies. The primary objective is to create an efficient and aesthetically pleasing system that not only allows urban dwellers to grow plants but also contributes to reducing the ambient temperature in apartment settings.